Pengaruh Kepemimpinan Instruksional Kepala Sekolah terhadap Kinerja Guru: Kajian Literatur - Rifka Jalal; Ernawati Ernawati; Jonni Mardizal (Departement of Mathematics Education, 2025)
This study aims to explore the influence of principal leadership style on teacher performance in Vocational High Schools (SMK) through the Systematic Literature Review (SLR) approach. This study involved 10 articles published in the period 2019–2024 using the keywords